1979
DOI: 10.3382/ps.0580900
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Fat on Energy Utilization by Laying Hens

Abstract: Feed grade fat was included at levels of 2 to 6% in corn-based laying hen rations and at levels of 3 to 6% in laying hen rations containing 8% wheat middlings. Added fat did not affect rate of egg production or average egg weight during the 196-day experiments. Feed consumption and efficiency of feed utilization were improved by added fat. Ration metabolizable energy (ME), as measured experimentally, was increased more than expected on the basis of commonly accepted ME values of feed grade fat when fat levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Two possible causes of this apparent improvement have been suggested. Although ME values of fat exceeding their GE have been reported in experiments with various classes of poultry, where either or both of these factors have been implicated (Cullen, Rasmussen and Wilder, 1962;Gomez and Polin, 1974;Sibbald and Kramer, 1977;Sell, Tenesaca and Bales, 1979;Mateos and Sell, 1980a), reasons for this observation in the present experiment are not apparent. Secondly, an improvement in the absorption of the non-oil component of the basal diet by the added oil is possible (Gomez and Polin, 1974;Mateos and Sell, 1980 b, c and d).…”
Section: Effect Of Age On Dietary Energy and Nutrient Utilizationcontrasting
confidence: 49%
“…Two possible causes of this apparent improvement have been suggested. Although ME values of fat exceeding their GE have been reported in experiments with various classes of poultry, where either or both of these factors have been implicated (Cullen, Rasmussen and Wilder, 1962;Gomez and Polin, 1974;Sibbald and Kramer, 1977;Sell, Tenesaca and Bales, 1979;Mateos and Sell, 1980a), reasons for this observation in the present experiment are not apparent. Secondly, an improvement in the absorption of the non-oil component of the basal diet by the added oil is possible (Gomez and Polin, 1974;Mateos and Sell, 1980 b, c and d).…”
Section: Effect Of Age On Dietary Energy and Nutrient Utilizationcontrasting
confidence: 49%
“…However, the calculated ME value for the corn-soybean basal diet probably overestimated the true ME for broiler breeders, because broiler breeders appear to be able to derive less ME from a corn-soybean diet than Leghorn hens, which have been used for estimating ME of feedstuffs (Spratt and Leeson, 1987a). Conversely, Sell et al (1979) have shown that the ME value for the added fat diets were probably underestimated, because added fat increases the ME value of omer energy components, producing an extra-caloric effect. Nevertheless, the ME intakes fall within the range of previously reported optimal intakes.…”
Section: Resultsmentioning
confidence: 92%
“…This overall trend was reflected in rising AME values. The ME values of dietary fats were reported to exceed theoretical limits (Cullen et al, 1962;Gomez and Polin, 1974;Sibbald and Kramer, 1977;Sell et al, 1979;Mateos and Sell, 1981a) or to exert an extrametabolic effect (Mateos and Sell, 1981a) reflected in improved efficiencies of growth (Jensen et al, 1970). Most investigators attributed this extra value of dietary lipids to be due to an enhanced absorption of nonlipid, dietary components.…”
Section: Discussionmentioning
confidence: 94%